Kinetic of CO2 Decomposition by Gliding Arc Plasma - Indarto, Antonius; Choi, Jae-Wook; Hwaung; Song, Hyung Keun (ASEAN Journal of Chemical Engineering, 2006)
Decomposition of carbon dioxide (C02) by gliding arc plasma was examined. The plasma reactor was consisted of two triangles stainless steel plates which was connected to a 20 kV AC power supply. The gas entered through a nozzle tube from the upstream cylinder reactor and exit at the downstream of the reactor. The effect of total gas flow rates have been used to study the chemical process reaction in gliding plasma system. The model of active-chemical kinetic of C02 decomposition was built to explain the way of plasma reaction. Experiment results indicate the conversion of C02 reached 18% at the total gas flow rate of 1.5’ 10.5m3s’1and produced CO and 02 as the main gaseous final products.